Long-run Overseas Portfolio Diversification Benefits and Opportunities of Asian Emerging Stock Markets and Developed Markets - LINGARAJA, Kasilingam; SELVAM, Murugesan; VASANTH, Vinayagamoorthi; RAJESH RAMKUMAR, Ramachandran (International Journal of Economics and Financial Issues, 2015)
The international portfolio diversification is a function of correlation of equity markets across countries and the amount of correlation one market has with another, decides the scope of portfolio diversification. The market having high correlation with other markets generally has less scope for portfolio diversification. This research study investigated the existence of long run portfolio diversification benefits and opportunities of eight emerging stock markets in Asia and three top, benchmark index of Developed Markets. Models such as Factor Analysis, Principal Component (PC) and Maximum Likelihood (ML), Correlation Matrix and Graphical Price Movement Diagram were used for estimating the portfolio diversification opportunity and benefits. It is suggested from overseas portfolio diversification analysis that in Asian emerging stock markets (especially China, India, Malaysia, Taiwan, Indonesia and Thailand), there are good opportunities for overseas portfolio diversification and the investors may earn high return. Keywords: Asian Emerging Stock Markets; Developed Markets; Principal Component Method (PCM); Maximum Likelihood (ML); Overseas Portfolio Diversification Opportunities and Benefits. JEL Classifications: F21; F37; G11; G15